Understanding leadership among senior enrolment management leaders and their followers: a multiple case study - Langston, R. J. (University of the Free State, 2017)
Higher education in the United States of America is undergoing significant transformation. Still feeling the effects of the “Great Recession”, states have cut back significantly on funding for higher education. In the USA, one specific department assumes responsibility as the highest level authority for enrolling students to the school. This department, called Enrolment Management (EM), is accountable for recruiting academically prepared students to the institution. Heading the offices is the EM leader. The success or failure of recruiting a viable and high academically achieving class ultimately rests with the EM leader. Through the use of multiple case study, this research effort sought to understand how higher education administrators serving in the role of senior EM leader describe their own style of leadership as well as how their subordinates perceived their leaders leadership style as expressed through the framework of the Kouzes and Posner (K&P) Five Practices of Exemplary Leadership. Quantitative findings revealed that each of the EM leaders demonstrated all five practices of K&P. Enabling Others to Act and Challenging the Process were viewed as the top leadership practices that the leaders engaged in with their staff, followed by Encouraging the Heart and Inspiring a Shared Vision. The least practiced leadership behaviour that EM leaders demonstrated was Modelling the Way. Qualitative analysis was further utilized in this study and numerous themes emerged. EM leaders perception that people mattered and the act of setting the example in the office was imperative to each of them. Effectively communicating institutional mission and moving staff towards ‘something big’ were also very important to these leaders. Changing the status quo and thinking outside the box as well as empowering others, building trust and helping people grow in their roles defined success for the leaders. Finally, rewards, recognition and celebration for staff were particularly valued by the leaders. Qualitative analysis was also utilised with followers (subordinates) of the SEM leaders to more readily understand their perceptions of their leader’s leadership style. Numerous themes emerged that illuminated what the followers of the leaders believed were their (leaders) most important behaviours. Followers consistently reported that their leaders who engaged in a practise of getting people excited about the future and treating others just like one of them were viewed as positive management traits. Followers also appreciated a leader who challenged the process, took risks, proposed new ideas to staff, and empowered others. Finally, followers believed that a true leader was one who was supportive and caring, and values recognition and reward.
Keywords: Universities and colleges -- Unites States; College attendance -- United States; Education, Higher -- United States; Educational leadership -- United States; Thesis Ph.D. (School of Higher Education Studies))--University of the Free State, 2017